Accountability e transparência no Sistema “S”: análise de conteúdo, publicização e comparabilidade - Oliveira, Sergio Luiz de (2021)
Widely discussed in the political sphere and throughout society, the theme of transparency has been given special attention to the entities of the “S” System, in order to make clear the actions of these entities and their managers. In a broad sense, the theme of transparency is associated with the theme of accountability, which refers to the responsibility of managers in the accountability process, who have been using electronic means for this purpose, creating the link "Transparency" on their websites, influenced by largely due to the determinations of the control bodies, CGU and TCU. It was found, throughout this work, that the measures adopted with the aim of transparency are not always satisfactory, in addition to validating the view of authors referenced in this work that the influences of the state and supervised bodies are the main motivators for the promotion of accountability. In this sense, this work sought to ascertain the level of transparency obtained by the entities that make up the S System, through a methodology adapted from Burgarelli (2015), used in studies on the same theme. This work, based on exploratory and descriptive research, used the portals of the entities of the S System, at the national level, raising the information inserted in the portals, in two aspects, quantitative, in compliance with the determinations that define the contents to be exposed, and qualitative, verifying how information is exposed, measuring the feasibility of access and use of data by interested parties. There was a need for improvements in the portals, especially with regard to the qualitative aspects of information, enabling access and use of data. As a result, the entities that make up the S System were classified by the level of transparency obtained by applying the aforementioned methodology. As for the quantitative aspects, there was a lack of data as required. There was also a big difference between the entities, in the way the information has been published. It is also noted, in line with the literature, that the evolution of accountability will occur as society is aware and involved, demanding accountability from public managers